Electrical inhibition of Purkinje cells in the cerebellum of the rat. - Korn, H (Proc Natl Acad Sci U S A, 1980)
Monosynaptic activation of cerebellar Purkinje cells by a volley of parallel-fiber impulses is followed by a powerful disynaptic chemical inhibition mediated by molecular layer interneurons, including basket cells. Active zone established by basket preterminal axons on the body surface of the Purkinje cell account for this inhibition. However, morphological studies indicate that branches of the presynaptic fibers further descend along the initial segment of the Purkinje axon. Terminals from several basket cells converge and encapsulate each initial segment with a peculiar architectural structure that is reminiscent of that characterizing the axon cap of the teleost Mauthner cell. Because no function has yet been attributed to this pinceau, we have reanalyzed the successive Purkinje cell responses to activation of their presynaptic elements. Electrophysiological data provided by field-potential and single-unit measurements indicate that the classical phases of excitation and inhibition after a parallel-fiber volley are preceded by a brief inhibition of the Purkinje cells. Transmembrane hyperpolarizing potentials that exhibit the characteristics expected of electrically mediatd potentials underlie this early phase of inhibition; their properties are consistent with the hypothesis that they are generated by currents through terminals of nearby basket cells. Therefore, these hyperpolarizations, which are similar in their mechanism of generation to those described in the Mauthner cell system, represent a known case of electrical inhibition in the mammalian central nervous system.